Budaya, Pariwisata, dan Komersialisasi Tradisi dalam Pacu Jawi Sebagai Cerminan Hybriditas Sosial di Tanah Datar - Irvan, Arief; Nurdiani, Silvana; Darmansyah, Darmansyah; Syukri, Alfi (Metta : Jurnal Ilmu Multidisiplin, 2025)
Pacu Jawi was originally a post-harvest tradition of the Minangkabau community, rooted in agrarian values and functioning as a sacred cultural celebration as well as a form of communal entertainment. With the expansion of cultural tourism, Pacu Jawi has undergone a significant transformation in both function and meaning, evolving into a key tourism attraction in Tanah Datar Regency. This study aims to analyze the transformation of Pacu Jawi from an agrarian-based cultural tradition into a commodified tourism product and to identify the forms of social hybridity that emerge through interactions between local cultural practices and the demands of the tourism industry. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation across four nagari that regularly host Pacu Jawi. The findings reveal that Pacu Jawi has experienced commodification that shifts its cultural meaning from a ritual practice to an economically oriented tourism spectacle. This process produces a hybrid cultural space in which traditional values, customary symbols, and local aesthetics intersect with the expectations of tourists, digital media, and global tourism dynamics. Consequently, Pacu Jawi now fulfills a dual role: as a preserved Minangkabau cultural heritage and as a strategic cultural identity used to promote Tanah Datar within the contemporary tourism landscape.